Using Comics as A Learning Media to Improve EFL Vocabulary: MAN 1 Lamongan Students’ Perspectives - Zuhria Nafisa; Arinatus Safitri; Muhammad Amirul Amin; Rakhmawati Rakhmawati; Yayuk Mukhayatin (Prodi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Darul Ulum Lamongan*, 2021)
Abstract In a classroom, educators are required to create or apply creative and innovative media that will influence successful learning outcomes. Comics have long been considered an interesting medium to make students engaged in learning EFL. The existing studies have investigated the effectiveness of comics in increasing students’ vocabulary acquisition through a series of tests, yet little information is explored to know how the students’ perceive comics as the best media to improve EFL attainment. This research involved 22 students from MAN 1 Lamongan by answering the questionnaire. The aim of this journal is to determine students' perspectives on the use of comics in their learning and to provide knowledge about whether students agree if comics are applied to them. From the finding it can be known that the comic has a positive result from the student perspective to be a learning medium that can improve student vocabulary. The expectation of this study is that teachers can start to use comics as a learning media to improve student vocabulary.